2020
DOI: 10.3390/v12010071
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis Uncovers a Vast Diversity in Intracellular Viral Defective Interfering RNA Content Affecting the Large Cell-to-Cell Heterogeneity in Influenza A Virus Replication

Abstract: Virus replication displays a large cell-to-cell heterogeneity; yet, not all sources of this variability are known. Here, we study the effect of defective interfering (DI) particle (DIP) co-infection on cell-to-cell variability in influenza A virus (IAV) replication. DIPs contain a large internal deletion in one of their eight viral RNAs (vRNA) and are, thus, defective in virus replication. Moreover, they interfere with virus replication. Using single-cell isolation and reverse transcription polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 63 publications
(93 reference statements)
1
25
0
Order By: Relevance
“…The total amount of IAV particles was quantified using a hemagglutination assay and was expressed as log 10 hemagglutinin units/100 μL (log 10 HA units/100 μL) (Kalbfuss et al 2008). PFU were determined by a plaque assay, conducted as described previously (Hein et al 2021a; Hein et al 2021b; Kupke et al 2020). Here, for the quantification of released infectious virus particles in the interference assay, parental adherent MDCK cells were used, only allowing propagation of STVs.…”
Section: Methodsmentioning
confidence: 99%
“…The total amount of IAV particles was quantified using a hemagglutination assay and was expressed as log 10 hemagglutinin units/100 μL (log 10 HA units/100 μL) (Kalbfuss et al 2008). PFU were determined by a plaque assay, conducted as described previously (Hein et al 2021a; Hein et al 2021b; Kupke et al 2020). Here, for the quantification of released infectious virus particles in the interference assay, parental adherent MDCK cells were used, only allowing propagation of STVs.…”
Section: Methodsmentioning
confidence: 99%
“…Influenza A virus (IAV) defective interfering particles (DIPs) were previously proposed for antiviral treatment against IAV infections [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], but also for pan-specific treatments of other respiratory viral diseases [ 23 , 24 ]. IAV DIPs typically carry a large internal deletion in their genome, rendering them defective in virus replication [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have recently used dual scRNA-seq to profile virally infected cells and draw insights from transcriptome information [38][39][40][41][42]. O'Neal et al revealed the feasibility and value of West Nile Virus-(WNV-) inclusive scRNA-seq as a method for single-cell transcriptomics and WNV RNA detection [38].…”
Section: 2mentioning
confidence: 99%